(untitled) (International Journal of Biomedical and Advance Research, 2015)
Background and objective: exposure to lead continues to a serious public problem. The objective is to elucidate the effect of lead acetate exposure on serum Concentration of urea and creatinine in adult female rats. Methods: Forty eight adults female rats divided in to four groups (12 rats/group) .Group 1, (T1) ,given date palm pollen (150 mg/kg. B.W.) Group 2,(T2) given lead acetate (10mg/kg. B.W.), group 3, (T3) given lead acetate (10mg/kg.B.W.) and date palm pollen (150 mg/kg. B.W) for 6 weeks, Group 4(Control) ,given distilled water. Serum concentration of urea and creatinine was evaluated via ELISA method for all groups. Results: The mean concentration of urea showed no significant difference between,(T1) and (T3) while in T2 a significant (p o.o5) increase in urea concentration compared to T1and T3 . There was no significant difference within groups in urea concentration. Group (T1) exposed to DPP showed no significant decrease in serum creatinine on zero,14 , 28 day and 42 day post exposure respectively . Group (T2) exposed to lead acetate showed significant increase of creatinine concentration compared with control and (T1) group .Group (T3) showed significant decrease in creatinine levels compared with T2 group and these levels become closely to control group. Histological changes indicated that DPP significantly meliorate the toxic effects of lead acetate in glomeruli, collecting tubules associated with obvious decrease in inflammatory response. Conclusion: DPP has the ability to counteract the toxic effect of lead acetate associated with improvement of renal histology and serum concentration of urea and creatinine.